The Application of Think Pair Share to Enhance Vocabulary Mastery - Syahrir L; La Baba; Muh Tamrin; Kamal Kamal; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The study's goal was to see if using think-pair-share to enhance students’ vocabulary mastery was beneficial. The pre-experimental approach was used in this study. MA YMPI Rappang's population was in its second year. The total number of pupils in the population was 65 (XI IPA=19, XI IPS 1= 24, XI IPS 2 = 22), and one class was chosen as a sample using cluster random sampling. This class had a total of 24 students (XI IPS 1). The vocabulary test was the tool employed in this study. The findings of this research revealed that the pre-test received a mean score of 25.91, while the post-test received a mean score of 60.00. This revealed that the pre-test and post-test scores differed significantly. The t-test value (15.112) was higher than the t-table value (2.069). This signifies that HO was turned down and H1 was chosen. The study found that teaching vocabulary utilizing the think-pair-share method helps improve students' vocabulary knowledge among MA YMPI Rappang second-year students.